Effect of lateral septum vasopressin administration on reward system neurochemistry and amphetamine-induced addictive-like behaviors in female rats - Gárate-Pérez, Macarena Francisca; Cáceres-Vergara, Daniela; Tobar, Francisca; Bahamondes, Carolina; Bahamonde, Tamara; Sanhueza, Claudia; Guzmán, Fanny; Sotomayor-Zárate, Ramón; Renard, Georgina M. (Frontiers in Pharmacology, 2024)
The chronic use of psychostimulants increases the risk of addiction and, there is no specific pharmacologic treatment for psychostimulant addiction. The vasopressin (AVP) system is a possible pharmacological target in drug addiction. Previous results obtained in our laboratory showed that amphetamine (AMPH) treatment decreases lateral septum (LS) AVP levels in male rats, and AVP microinjection in LS decreases addictive-like behavior. The aim of the present work was to investigate the effect of AMPH treatment on LS AVP levels and the effect of LS AVP administration on the expression of AMPH-conditioned place preference (CPP) in female rats. The secondary objectives were to study the effect of LS AVP administration on LS GABA and glutamate release in male and female rats and on nucleus accumbens (NAc) dopamine (DA) release in female rats.Female rats were conditioned with AMPH (1.5 mg/kg i.p.) or saline for four days. Conditioning with AMPH did not change LS AVP content in females. However, AVP microinjection into the LS decreased the expression of conditioned place preference (CPP) to AMPH. Glutamate and GABA extracellular levels in the LS induced by AVP were studied in males and females. NAc GABA and DA extracellular levels induced by LS AVP microinjection in female rats were measured by microdialysis.In males, AVP perfusion produced a significant increase in LS GABA extracellular levels; however, a decrease in GABA extracellular levels was observed in females. Both in males and females, LS AVP perfusion did not produce changes in LS glutamate extracellular levels. Microinjection of AVP into the LS did not change GABA or DA extracellular levels in the NAc of females. Therefore, AVP administration into the LS produces different LS-NAc neurochemical responses in females than males but decreases CPP to AMPH in both sexes. The behavioral response in males is due to a decrease in NAc DA levels, but in females, it could be due to a preventive increase in NAc DA levels.